Competitive Advantage: Influence of Innovativeness, Marketing Sensing Capabilities and Brand Image on Marketing Performance MSE’s - Nurudin Nurudin; Muyassarah Muyassarah; Laily Nur Asyifa (At-Taqaddum, 2021)
Marketing performance is one of the important factors in realizing business goals. Marketing performance is influenced by various factors. This study aims to determine the effect of innovation, marketing sensing ability and brand image on competitive advantage to realize marketing performance. This research is based on a case study of Batik MSEEs in Central Java. This study uses data analysis The Structural Equation Modelling (SEM) with the number of samples used as many as 169 respondents. The results of this study indicate that innovation, marketing sensing ability, brand image, have a positive and significant effect on competitive advantage. Innovation, marketing sensing ability, brand image, competitive advantage proved to have a significant positive effect on Marketing Performance. Thus, to improve marketing performance, MSMEs need to improve innovation, marketing sensing capabilities and brand image for competitive advantage.